Circulating Monocyte-Like Myeloid Derived Suppressor Cells and CD16 Positive Monocytes Correlate With Immunological Responsiveness of Tuberculosis Patients - Amiano, Nicolás O.; Pellegrini, Joaquín M.; Morelli, María P.; Martinena, Camila; Rolandelli, Agustín; Castello, Florencia A.; Casco, Nicolás; Ciallella, Lorena M.; de Casado, Graciela C.; Armitano, Rita; Stupka, Juan; Gallego, Claudio; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Alterations of myeloid cell populations have been reported in patients with tuberculosis (TB). In this work, we studied the relationship between myeloid-derived suppressor cells (MDSC) and monocytes subsets with the immunological responsiveness of TB patients. Individuals with active TB were classified as low responders (LR-TB) or high responders (HR-TB) according to their T cell responses against a cell lysate of Mycobacterium tuberculosis (Mtb-Ag). Thus, LR-TB, individuals with severe disease, display a weaker immune response to Mtb compare to HR-TB, subjects with strong immunity against the bacteria. We observed that LR-TB presented higher percentages of CD16 positive monocytes as compared to HR-TB and healthy donors. Moreover, monocyte-like (M-MDSC) and polymorphonuclear-like (PMN-MDSC) MDSC were increased in patients and the proportion of M-MDSC inversely correlated with IFN-γ levels released after Mtb-Ag stimulation in HR-TB. We also found that LR-TB displayed the highest percentages of circulating M-MDSC. These results demonstrate that CD16 positive monocytes and M-MDSC frequencies could be used as another immunological classification parameter. Interestingly, in LR-TB, frequencies of CD16 positive monocytes and M-MDSC were restored after only three weeks of anti-TB treatment. Together, our findings show a link between the immunological status of TB patients and the levels of different circulating myeloid cell populations.